Comparative analysis of salivary sialic acid levels in patients with chronic obstructive pulmonary disease and chronic periodontitis patients: A biochemical study - Surekha Rathod; Tony Shori; Trupti Satish Sarda; Anubha Raj; Padmaja Jadhav (Wolters Kluwer Medknow Publications, 2018)
Aim: Sialic acid plays a central role in the functioning of biological systems, in stabilizing the glycoproteins and cellular membranes, assisting in cell-cell recognition and interaction. The aim of this study is to evaluate and compare the periodontal health status and salivary Sialic acid levels in patients suffering from chronic obstructive pulmonary diseases (COPD) and chronic periodontitis patients. Materials and Methods: Ninety subjects were included in the study, which were divided into the following groups, 30 in each group. Group 1: patients suffering from COPD and chronic periodontitis, Group 2: periodontitis patients without any systemic diseases Group 3: healthy subjects. Unstimulated whole saliva samples were collected around 9-10 AM; 2 h after the subjects had breakfast. The sialic acid content was determined by a combined modification of the thiobarbituric acid method of Skoza and Mohos. Results: The mean salivary sialic acid levels were least in the healthy group followed by the periodontitis group, and it was highest in the COPD group. Conclusions: We can thus conclude that promotion of dental care knowledge is very much essential in the prevention and treatment of COPD. Thus, estimation of levels of salivary sialic acid can be used as an adjunct to diagnose the current periodontal disease status and to assess the treatment outcomes in subjects with COPD and chronic periodontitis.